(2-Aminoaryl)iminophosphoranes as Versatile Starting Materials for the Synthesis of 1-Aryl-2-trifluoromethylbenzimidazoles - Walewska-Królikiewicz, Magdalena; Wilk, Bogdan; Kwast, Andrzej; Wróbel, Zbigniew (Synlett, 2022)
A new route to 2-(trifluoromethyl)benzimidazoles is described which involves the condensation of (2-arylamino)iminophosphoranes with trifluoroacetyl esters or trifluoroacetic anhydride. The method allows the synthesis of the title compounds from simple nitroarenes without the use of separate reduction steps and metallic reagents or expensive catalysts.
Keywords: cyclization; condensation; heterocycles; annulation; benzimidazoles